EVALUATING GEOGRAPHY BASIC COMPETENCIES IN THE 2013 CURRICULUM IN RELATION TO THE DEVELOPMENT OF STUDENTS’ SPATIAL LITERACY - Edies Rizqi Adelia; Maulida Afna Musoffa; Shinta Ester Debora; Muhammmad Zid; Wini Mustikarani (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the extent to which the Basic Competencies (KD) in Geography in the 2013 Curriculum contribute to strengthening students' spatial literacy. The study used a qualitative descriptive approach with content analysis techniques on curriculum documents and source triangulation. The results showed that the Basic Competencies in Geography in grades X, XI, and XII have varying levels of strengthening spatial literacy. Grade X plays a role in building a foundation for spatial understanding related to geosphere phenomena. Grade XI strengthens understanding of spatial interactions through materials on resource distribution, population dynamics, and human-environment relationships. Meanwhile, grade XII is the level with the greatest contribution to spatial literacy through materials on remote sensing, Geographic Information Systems (GIS), rural-urban spatial patterns, and zoning. Although the structure of the Basic Competencies shows gradual development, it is not entirely consistent in demanding advanced spatial skills, especially at earlier levels. These findings emphasize the importance of strengthening learning strategies and supporting school facilities to maximize the potential of Basic Competencies in building students' spatial literacy.